Increasing Learning Result of Pythagoras Material through Geogebra Application Media of VIII4 Grade Students at SMP Negeri 12 Parepare - Mustafa, Sriyanti; Sulvianti, Sulvianti; Saputra, Adiwinata (MEJ (Mathematics Education Journal), 2018)
This research was a classroom action research that aims to know that theused of geogebra application media could improved the learning outcomesof phytagoras material of VIII.4 grade students at SMP Negeri 12Parepare.The subjects of this research were students of class VIII.4 at JuniorHigh School 12 Parepare which amounted to 20 people. This research wasconducted in two cycles, each of which was three meetings of the learningprocess and one meeting in conducted the result of learning test ofphytagoras material. The data collection techniques used in this researchwere test techniques and observation techniques.Based on the results of theresearch and discussion for two cycles, it can be concluded that the resultsof learning materials phytagoras on students of class VIII.4 SMP Negeri 12Parepare increased from cycle I to cycle II. This was indicated by: (1)Average score of learning result of phytagoras material of student that was77,65 in cycle I increase to 91,54 in cycle II. (2) The achievement ofstudents' learning mastery from cycle I was 70% increased to 100% in cycleII, or completely classical. (3) The increased of percentage of studentactivity average in learning process that was 43,33% in cycle I become53,33% in cycle II.